Nursing management of a patient with massive hemorrhage during spinal operation under general anesthesia (1例全身麻醉下脊柱手术患者术中大出血的护理管理) - YANG Mei (杨梅); WANG Wencan (王文璨); YANG Qi (杨琪) (Association of Integrative Nursing, 2021)
This paper reported the nursing management of a patient with massive hemorrhage during spinal operation under general anesthesia. Intraoperative fluid supplementation was performed as fluid loss and hypovolemia before the operation. A massive hemorrhage had occurred as accidental damage to the vein, and targeted treatment and nursing interventions were carried out to stabilize the patient's vital signs. (本文报告1例全身麻醉下脊柱手术患者术中大出血的护理管理经验。该患者术前存在容量不足, 术中给予积极补液。因术中意外损伤静脉血管未及时有效止血而出现大出血, 经积极处理后患者情况好转, 术后安全送入ICU。)